To Treat or Not to Treat? This Is the Question… About the Incidental Finding of Double Sinus of Valsalva Aneurysm in A 91-Year-Old Woman - Marco,Luca Di (2022)
ABSTRACT Sinus of Valsalva aneurysm is a very uncommon clinical finding and often requires emergency surgery due to its high risk of rupture. This educational text reports the case of a 91-year-old Italian women who was incidentally discovered to have a huge double aneurysm of the sinuses of Valsalva.